Dysregulation of deubiquitinases in gastric cancer progression - Xu, Zifan; Lei, Zi; Peng, Shilan; Fu, Xiaonan; Xu, Yuanyuan (Frontiers in Oncology, 2024)
Gastric cancer (GC), characterized by a high incidence rate, poses significant clinical challenges owing to its poor prognosis despite advancements in diagnostic and therapeutic approaches. Therefore, a comprehensive understanding of the molecular mechanisms driving GC progression is crucial for identifying predictive markers and defining treatment targets. Deubiquitinating enzymes (DUBs), also called deubiquitinases, function as reverse transcriptases within the ubiquitin-proteasome system to counteract protein degradation. Recent findings suggest that DUB dysregulation could be a crucial factor in GC pathogenesis. In this review, we examined recent research findings on DUBs in the context of GC, elucidating their molecular characteristics, categorizations, and roles while also exploring the potential mechanisms underlying their dysregulation in GC. Furthermore, we assessed the therapeutic efficacy of DUB inhibitors in treating malignancies and evaluated the prevalence of aberrant DUB expression in GC.